Impact of Genital Infections and Antibiotic Use on Incidence of Preterm Birth: A Retrospective Observational Study - Daniela Teodora Marti; Felix Bratosin; Ovidiu Rosca; Roxana Folescu; Cosmin Citu; Adrian Ratiu; Zoran Laurentiu Popa (Antibiotics, 2024)
This study investigates the complex interplay among genital infections, antibiotic usage, and preterm birth. This study aims to identify common genital pathogens associated with preterm births, assess the impact of various antibiotic treatments on pregnancy outcomes, and understand antibiotic resistance patterns among these pathogens. This study included 71 pregnant women who experienced preterm birth and 94 women with genital infections who delivered at term. Various maternal characteristics, medical history, signs and symptoms, gestational weight, gestational age, type of birth, vaginal pH, Nugent scores, and vaginal flora were analyzed. Antibiotic resistance patterns of isolated microorganisms were also examined. The prevalence of sexually transmitted diseases (STDs) and genital herpes was significantly higher in the preterm group. Preterm births were associated with fever, pelvic pain, vaginal spotting, and fatigue. Vaginal pH levels and Nugent scores were significantly higher in the preterm group, indicating disturbed vaginal flora. The presence of Extended-Spectrum Beta-Lactamases (ESBLs) was a particularly strong risk factor, increasing by more than four times the odds of preterm birth (OR = 4.45, p = 0.001). Vancomycin-Resistant Enterococci (VRE) presence was another critical factor, with a four-fold increase in the odds of preterm birth (OR = 4.01, p = 0.034). The overall presence of Multidrug-Resistant (MDR) organisms significantly increased the odds of preterm birth (OR = 3.73, p = 0.001). Specific pathogens like Chlamydia trachomatis (OR = 3.12, p = 0.020) and Mycoplasma hominis (OR = 3.64, p = 0.006) were also identified as significant risk factors. Ureaplasma urealyticum also showed a significantly higher risk of preterm birth (OR = 2.76, p = 0.009). This study highlights the importance of screening for and treating genital infections during pregnancy, especially STDs and genital herpes, as they can significantly increase the risk of preterm birth. Additionally, the presence of specific microorganisms and antibiotic resistance patterns plays an essential role in preterm birth risk. Early detection and targeted antibiotic treatment may help mitigate this risk and improve pregnancy outcomes.